Simple binding of protein kinase A prior to phosphorylation allows CFTR anion channels to be opened by nucleotides - Mihályi, Csaba (Proc Natl Acad Sci U S A, 2020)
The Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) anion channel is essential for epithelial salt–water balance. CFTR mutations cause cystic fibrosis, a lethal incurable disease. In cells CFTR is activated through the cAMP signaling pathway, overstimulation of which during cholera leads to CFTR-mediated intestinal salt–water loss. Channel activation is achieved by phosphorylation of its regulatory (R) domain by cAMP-dependent protein kinase catalytic subunit (PKA). Here we show using two independent approaches––an ATP analog that can drive CFTR channel gating but is unsuitable for phosphotransfer by PKA, and CFTR mutants lacking phosphorylatable serines––that PKA efficiently opens CFTR channels through simple binding, under conditions that preclude phosphorylation. Unlike when phosphorylation happens, CFTR activation by PKA binding is completely reversible. Thus, PKA binding promotes release of the unphosphorylated R domain from its inhibitory position, causing full channel activation, whereas phosphorylation serves only to maintain channel activity beyond termination of the PKA signal. The results suggest two levels of CFTR regulation in cells: irreversible through phosphorylation, and reversible through R-domain binding to PKA––and possibly also to other members of a large network of proteins known to interact with the channel.